Knowledge of HIV pre-exposure prophylaxis (PrEP) among students – A narrative review - Snopkowska, Aleksandra; Mężyk, Julia; Gołda, Joanna; Gacka, Piotr; Dołęga, Marcin; Dróżdż, Olgierd; Musialska, Dominika; Wójcik, Paulina; Kuderska, Natalia (Journal of Education, Health and Sport, 2024)
Acquired Immunodeficiency Syndrome (AIDS) has been a global epidemic since the 1980s, with the Joint United Nations Programme on HIV and AIDS (UNAIDS) aiming to eliminate it as a public health threat by 2030. As of 2017, 36.9 million individuals were living with HIV worldwide, making HIV infection a leading cause of death globally. Pre-exposure prophylaxis (PrEP) is a highly effective biomedical prevention method that can reduce the risk of HIV transmission by over 90% when taken consistently. This review examines the awareness and knowledge of PrEP among students, focusing on variations across gender, race, sexual orientation, study type, university type, and country of residence. A literature search conducted in the MEDLINE database between February and March 2024 identified 26 relevant studies published in the last ten years. Findings reveal significant disparities in PrEP awareness and knowledge, influenced by factors such as field of study and geographic location. While healthcare students generally show higher awareness levels, gaps remain, particularly among non-healthcare students and in different regions. Targeted educational initiatives are crucial to enhance PrEP acceptance and utilization. Addressing these gaps is essential for improving HIV prevention efforts and ultimately achieving UNAIDS' 2030 objective.